The influence of health The education using the Ludo game on teenagers' knowledge about bullying at SMA Muhammadiyah 3 Palembang - Ranti Ayu Kartika; Ayu Dekawaty; Suzanna Suzanna (Masker Medika, 2024)
ABSTRACT Introduction: Adolescence is a transition period from childhood to adulthood that involves biological, cognitive, and social-emotional changes, the social-emotional process is reflected in aggressive actions against peers that cause bullying. The importance of knowledge in adolescents can encourage awareness to act according to the knowledge they have, therefore it is necessary to have creative, innovative and interesting education, one of which is the ludo game method. Research Objective: to determine the influence of health education with Ludo games on adolescents' knowledge about Bullying at SMA Muhammadiyah 3 Palembang. Research method: This study is a quantitative research, using a pre-experimental design with a one-group pretest and posttest approach with a sample of 35 respondents and using a questionnaire on the level of knowledge of bullying and ludo game media. Research results: There is an effect after being given health education with